Organocatalyst system for disubstituted carbonates from cycloaddition between CO2 and internal epoxides. (March 2018) - Hirose, Takuji; Qu, Shujie; Kodama, Koichi; Wang, Xiangyong
Graphical abstract: Highlights: The 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) and n Bu4 NCl system shows high activity for disubstitued cyclic carbonates synthesis. Mild conditions: 1–4 atm CO2 and 100–120 °C without solvent. Cl − ion was shown to be more effective than Br ‒ and I ‒ due to its nucleophilicity and the steric hindrance of disubstituted epoxide. The combination of DBU and n BuCl was also presented as an alternative, still efficient and more economical catalytic system. Abstract: An organocatalyst system, 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) and n Bu4 NCl, was developed for the conversion of CO2 and internal epoxides to the corresponding disubstituted cyclic carbonates under rather mild conditions (1–4 atm of CO2 and 100–120 °C). Catalyst screening revealed that small Cl − opens epoxide rings more effectively than larger Br − and I − do when used as the counter anion of n Bu4 N +, suggesting that the steric hindrance of the internal epoxides is a factor. A practical and economical alternative system, DBU and n BuCl, is also presented.